VIOLATIONS OF NEUROCOGNITIVE FUNCTION IN ALCOHOL DEPENDENCE - Zhyvotovska, L.V. (World of Medicine and Biology, 2014)
The analysis of neuropsychological performance of higher mental functions, taking into account constitutional-typological features in 290 patients with alcohol dependence. The estimation of the severity of neurocognitive impairment in this group of patients.